The Influence of Cyclic Loading on the Extensibility of Human Hamstring Muscle-Tendon Units in Vivo - Dombroski, Erik (Auckland University of Technology, 2005)
The objective of this study was to investigate the influence of cyclic loading on the extensibility of hamstring muscle-tendon units in vivo.Study Design: A test-retest randomised controlled trial with repeated measures was undertaken.Background: Stretching has been commonly promoted to increase the passive extensibility of the muscle-tendon units, yet the mechanism behind its proposed effects remains ambiguous. In vivo studies of stretching have mostly been limited to the viscoelastic characteristic of stress-relaxation. Few studies have investigated the characteristic of creep. Animal and cadaver in vitro creep experiments have consistently shown increases in the length of the soft tissues, with associated changes in their resistance and stiffness. These results however, might not be representative of human muscle-tendon units under in vivo conditions. Additionally, those in vivo human studies that have investigated creep phenomenon have contrasting results. To date, no known in vivo study has examined passive cyclic loading of human hamstrings to a constant load level.Method: Using a repeated measures design the extensibility of the hamstring muscles were assessed by a passive knee extension test (PKE) to maximal stretch tolerance using a KinCom® dynamometer. Those participants in the intervention group underwent 45 continuous passive cyclic loadings as the KinCom® dynamometer moved the knee joint into extension until torque reached 85% of maximal passive resistance torque measured in the passive knee extension test. The control group sat quietly relaxed during the intervention period. Measurements of hamstring passive extensibility using the PKE test were repeated at the end of the intervention.Results: Following the intervention, the PKE test showed for the cyclic loading group there was a significant (p < 0.05) increase in both maximal passive resistance torque (mean 23%) and knee joint angle (mean 6.3%). A significant (p < 0.05) decrease in passive resistance torque (mean 11.8%) when re-measured at the baseline position of maximal passive knee angle was observed. A significant increase (p < 0.05) was found for passive stiffness over the final 10% of the knee torque-angle curve. No significant difference (p > 0.05) was found for passive stiffness for the full (100%) of the torque-angle curve. Of the control group, no significant differences (p > 0.05) were observed for all variables of the PKE test. Analysis of cycle one compared to forty-five of the cyclic loading intervention procedure showed a significant (p < 0.05) increase in both passive knee joint angle (mean 5.2%) and passive stiffness (mean 28.6%) over the final 10% of the knee joint torque-angle. No significant difference (p > 0.05) was found for passive stiffness across the full (100%) knee joint torque-angle.Conclusion: The findings of the current study demonstrated that after cyclic loading the hamstring muscles lengthened and became stiffer over the final gained range of knee joint motion. Although the current study cannot determine the mechanism behind the changes in the variables of interest, these findings do provide some evidence that most likely a combination of altered stretch tolerance and local mechanical effects within the muscle-tendon unit, i.e. creep lengthening were responsible.
Keywords: Stretching exercises; Knee; Muscles; Tendons; Hamstring muscles; Exercise science